Rubber Science A Modern Approach - Ikeda, Yuko (Springer Singapore, 2018)
This book is an up-to-date text on rubber science and is a breakthrough among many rubber-related publications. Emphasis is placed on the most modern scientific approaches to rubber science, departing from the usual detailed descriptions of trial-and-error results of traditional rubber technology. The book is a good introduction to modern rubber science both for graduate students and for more or less experienced rubber engineers for updating their way of thinking in handling of technological problems. Due to the increasing importance of pneumatic tires of vehicles and aircraft in modern transportation, this work will be of great use for general readers as well, including those who are concerned with sustainable development.